Impact of electric field on the linear, non-linear, and total optical properties of ZnO/Zn1−xMgxO pyramid quantum dot in the presence of an off-center donor atom - A. Bakdid; S. Chouef; M. Hbibi; R. Boussetta; A. El Moussaouy; O. Mommadi; C.A. Duque (Scientific African)
In this study, we focus on the effect of the electric field on the optical properties of a ZnO/Zn1−xMgxO pyramid quantum dot in the presence of an off-center donor atom. Using the effective mass approximation, the numerical solution of the Schrödinger equation was performed using the finite difference and element methods. Several enhancements and effects on the pyramid semiconductor geometry were investigated, indicating that the linear, non-linear, and total optical properties of pyramid quantum dots can be significantly modified by impurity position and external field. Our results show that the oscillator strength, matrix element, and energy transition are influenced by the position of the impurity as well as by the electric field intensity, which can modulate the absorption coefficient and relative refraction coefficient. These results aim to contribute to the fundamental understanding of the effects of the electric field on the optical properties of these nanostructures and their implications for the development of advanced optoelectronic devices.